The embodied self : movement and psychoanalysis - Bloom, Katya (Karnac, 2006)
By integrating principles from her background as a movement psychotherapist and movement analyst with key concepts from contemporary psychoanalysis, the author offers a new perspective on exploring the interrelationships between nonverbal and verbal 'articulation' in any therapy setting. The Embodied Self aims to provide a practical and experiential working model for developing therapists' embodied attentiveness, which will enhance their recognition of the sensori-affective manifestations of transference and countertransference. It will inform the work of psychotherapists and psychoanalysts, dance movement therapists, and body psychotherapists, as well as those involved in psychoanalytic observational studies. It will also be of great value to anyone interested in exploring the interrelationships between the psyche and the body.